Utilization of Online Learning Media Platforms During the Pandemic Covid-19 - Dewi Aprilia; M Wafiyul Ahdi (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to determine the effectiveness of the online learning media platform used in online learning during the Covid-19 pandemic at MTsN 3 Jombang. This research method is a qualitative research approach based on the philosophy of postpositivism. The data collection technique in this study used triangulation techniques and the results of qualitative research data analysis emphasized meaning rather than generalization. Retrieval of data source informants carried out purposive and snowball. The results of the research were then discussed through a literature review of relevant references and research findings so that several platforms were found that were used at MTsN 3 Jombang during online learning, namely Google Classroom, Google Form, Quizizz, Whatsapp, and Youtube. The results of this study are an increase in student learning outcomes during online learning and teachers at MTsN 3 Jombang state that an effective platform for online learning at MTsN 3 Jombang is Google Classroom.